In vitro Evaluation of Botanical Extracts, Chemical Fungicides and Trichoderma harzianum Against Alternaria brassicicola Causing Leafspot of Cabbage - Pun, Lok Bahadur; Chhetri, Kamal; Pandey, Anju; Poudel, Rajan (Nepalese Horticulture, 2020)
Alternaria leaf spot caused by Alternaria brassicicola is one of the destructive diseases of crucifers and causes considerable loss in the yield and quality of the produce. An experiment was conducted in in vitro to evaluate the efficacy of six botanical extracts at three concentrations i.e. 5%, 10% and 15%, six chemical fungicides at five different concentrations i.e. 50ppm, 100ppm, 250ppm, 500ppm and 1000ppm and Trichoderma harzianum against Alternaria brassicicola. The study was carried out using poisoned food technique for botanical extracts and chemical fungicides and dual culture technique for T. harzianum in Completely Randomized Design (CRD). Among botanical extracts, maximum inhibition (99.91%) of mycelial growth was observed in sweet flag at 15% concentration followed by 10% sweet flag (96.68%) and 5% sweet flag (93.64%) and minimum inhibition percent (5.61%) was observed in Lantana camara at 5% concentration. Hexaconazole proved to be the most effective chemical fungicide recording 100% growth inhibition at all the tested concentrations which was at par with1000 ppm metalaxyl + mancozeb (Kriloxyl Gold), 500 and 1000 ppm mancozeb and 1000 ppm carbendazim + mancozeb(SAAF)whereas, 50 ppm carbendazim was least effective in reducing fungal growth (7.16%). T. harzianum showed 65.02% inhibition of test fungus. The study indicated better performance of some chemical fungicides even at lower concentrations i.e. 100ppm and 250ppm. So, such effective fungicides could be used to minimize hazardous effect. Significant effect of some botanical extracts against pathogen growth suggests their application as potential control agent alternative to chemicals.